New Discorhabdin B Dimers with Anticancer Activity from the Antarctic Deep-Sea Sponge Latrunculia biformis - Li, Fengjie (Mar Drugs, 2020)
Latrunculia sponges represent a rich source of discorhabdin-type pyrroloiminoquinone alkaloids, a few of which comprise a dimeric structure. The anticancer-activity-guided isolation of the n-hexane subextract of the Antarctic deep-sea sponge Latrunculia biformis yielded the known compound (−)-(1R,2R,6R,8S,6’S)-discorhabdin B dimer (1) and two new derivatives, (−)-(1S,2R,6R,8S,6’S)-discorhabdin B dimer (2) and (−)-(1R,2R,6R,8S,6’S)-16’,17’-dehydrodiscorhabdin B dimer (3). The chemical structures of compounds 1–3 were elucidated by means of HR-ESIMS, NMR, [α](D), ECD spectroscopy, and a comparison with the previously reported discorhabdin analogs. Compounds 1 and 2 showed significant in vitro anticancer activity against the human colon cancer cell line (HCT-116), with IC(50) values of 0.16 and 2.01 µM, respectively. Compared to monomeric discorhabdins, dimeric discorhabdins are very rare in Nature. This study adds two new discorhabdin dimers (2 and 3) to this small pyrroloiminoquinone subfamily. This is also the first report of compound 1 as a natural product and the first assessment of its in vitro anticancer activity.